Safety and efficacy of Availa®Cr (chromium chelate of DL‐methionine) as a feed additive for dairy cows. (26th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Availa ® Cr (active compound: chromium chelate of DL‐methionine) as a feed additive for dairy cows. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) Panel was assigned to this mandate. The tolerance study did not show adverse effects with respect to body weight, milk yield, haematology and blood biochemistry up to the 10‐fold overdose of chromium from Availa ® Cr; however, owing to deficiencies in design and reporting of the study, it provided only supportive evidence on the safety of the additive. A safe level for dairy cows could be derived from a toxicological study with laboratory rodents. Taking all together, the FEEDAP Panel considers the maximum recommended use level (8 mg Cr from Availa ® Cr/cow per day; about 0.4 mg Cr/kg complete feed) as safe. Chromium DL‐Met shows a genotoxic activity in vitro that is not expressed in vivo after systemic exposure; although no data on genotoxicity at the site of contact are available, the Panel notes that chromium(III) is not carcinogenic and concludes that chromium DL‐Met is unlikely to pose a carcinogenic risk at levels occurring in the diet. The use of Availa ® Cr in feed of dairy cows up to the recommended supplementation level would not measurably increase consumer exposure to chromium(III), and therefore is safe for consumers. The additive poses a risk to users by inhalation, it is not an irritant to skin and eyes and should be considered a sensitiser. The use of the additive is not expected to pose a risk to the environment. Since only one study could be considered for the efficacy assessment, and three studies are required, the FEEDAP Panel cannot conclude on the efficacy of Availa ® Cr for dairy cows.